Matched-pair analysis: large-sized defects in surgery of lower limb nonunions - Findeisen, Sebastian; Schwilk, Melanie; Haubruck, Patrick; Ferbert, Thomas; Helbig, Lars; Miska, Matthias; Schmidmaier, Gerhard; Tanner, Michael Christopher (Journal of Clinical Medicine, 2023)
Background: The treatment of large-sized bone defects remains a major challenge in trauma and orthopaedic surgery. Although there are many treatment options, there is still no clear guidance on surgical management, and the influence of defect size on radiological and clinical outcome remains unclear due to the small number of affected patients. The aim of the present study was to determine the influence of defect size on the outcome of atrophic and infected nonunions of the tibia or the femur based on the diamond concept in order to provide recommendations for treatment guidance. Patients and Methods: All medical records, surgical reports, laboratory data and radiological images of patients treated surgically for atrophic or infected nonunions of the lower limbs (femur or tibia) between 1 January 2010 and 31 December 2020 were examined. Patients with proximal, diaphyseal or distal nonunions of the femur or tibia who were surgically treated at our institution according to the “diamond concept” and attended our standardised follow-up program were included in a database. Surgical treatment was performed as a one- or two-step procedure, depending on the type of nonunion. Patients with a segmental bone defect ≥5 cm were matched with patients suffering a bone defect <5 cm based on five established criteria. According to our inclusion and exclusion criteria, 70 patients with a bone defect ≥5 cm were suitable for analysis. Two groups were formed by matching: the study group (bone defect ≥5 cm; n = 39) and control group (bone defect <5 cm; n = 39). The study was approved by the local ethics committee (S-262/2017). Results: The mean defect size was 7.13 cm in the study and 2.09 cm in the control group. The chi-square test showed equal consolidation rates between the groups (SG: 53.8%; CG: 66.7%). However, the Kaplan-Meier curve and log-rank test showed a significant difference regarding the mean duration until consolidation was achieved, with an average of 15.95 months in the study and 9.24 months in the control group (α = 0.05, p = 0.001). Linear regression showed a significant increase in consolidation duration with increasing defect size (R2 = 0.121, p = 0.021). Logistic regression modelling showed a significant negative correlation between consolidation rate and revision performance, as well as an increasing number of revisions, prior surgeries and total number of surgeries performed on the limb. Clinical outcomes showed equal full weight bearing of the lower extremity after 5.54 months in the study vs. 4.86 months in the control group (p = 0.267). Conclusion: Surprisingly, defect size does not seem to have a significant effect on the consolidation rate and should not be seen as a risk factor. However, for the treatment of large-sized nonunions, the follow-up period should be prolonged up to 24 months, due to the extended time until consolidation will be achieved. This period should also pass before a premature revision with new bone augmentation is performed. In addition, it should be kept in mind that as the number of previous surgeries and revisions increases, the prospects for consolidation decrease and a change in therapeutic approach may be required.